Diversities of conservation agriculture technologies being adopted by rural farmers in sub-Saharan Africa region: a case study from Vibangalala extension planning area, Mzimba District, Malawi - Chidimbah Munthali, George N.; Puming, He; Banda, Lazarus Obed Livingstone; Ngulube, Peter Stephen Donald (Frontiers in Sustainable Food Systems, 2025)
BackgroundFood insecurity remains a significant challenge in many developing economies, including Malawi, where agriculture plays a crucial role in enhancing livelihoods, ensuring food security, and promoting rural development. This study investigates the diversity of conservation agricultural technologies (CATs) adopted by rural farmers in Vibangalala EPA, Malawi.MethodsA survey was conducted with 390 respondents utilizing a purposive sampling technique to capture insights on farmers’ awareness and adoption of CATs. Data analysis was performed using NVIVO software to compute frequency tables and percentages of categorical variables, with statistical significance set at p < 0.05.FindingsThe findings reveal that while 96.9% of farmers were aware of CATs, the actual adoption rates were significantly lower due to challenges such as high labour costs and limited resources. Specifically, intercropping was adopted by 36.92% of farmers, and organic manure by 29.49%. Conversely, mulching and mixed cropping saw much lower adoption rates at 7.8 and 2.56%, respectively. Key barriers to the adoption of CATs included innovation barriers, limited access to resources, and labour constraints.RecommendationsDespite farmers’ substantial knowledge of CATs, various constraints hinder their effective implementation. To enhance the adoption of these technologies, it is recommended that strategies be developed to address labour and resource limitations, including context-appropriate training programs, resource enhancement initiatives, and targeted promotional efforts focused on local farming systems.